RETENSI DALAM PENGAWETAN KAYU KURANG DIKENAL UNTUK BAHAN BAKU KAPAL TRADISIONAL - Cahyana, Budi Tri (Kementerian Perindustrian, 2014)
The wood stock nowdays is limited, so it is needed the effect to develop the making of boat wood using lesser known wood. In addressing the limited number of wood supply include wood from forest plantations as well as the people that potential is quite large for a variety of purposes. This research aims to make the process less wood preservation is known as the substitution of raw materials manufacture of traditional boats which of wood is jengkol (Pithecellobium jiringa Benth IC Nielsen), kupang (Ormosia sumatrana Prain), tarap (Artocarpus adoratissimus) and Acid (Mangifera applanata Kosterm). The utilization supported by the preservation process, using permethrin, parachem and impralit CKB. Concentration are used 5%, 10% and 15% by length of immersion respectively 10 days and 15 days. The results of the study showed that retention was likely to increase up to a concentration of 10%. The best retention was in kupang wood using 10% concentration parachem by 10 days immersion. Based on the research results of the four types of wood preserved with preservative resistant to all three compounds in marine wood borers.Keywords: Â wood of jengkol, kupang, tarap and acid, preservation, traditional boat